Anticonvulsant activity of Aloe vera leaf extract in acute and chronic models of epilepsy in mice. (20th November 2013) - Rathor, Naveen; Arora, Tarun; Manocha, Sachin; Patil, Amol N.; Mediratta, Pramod K.; Sharma, Krishna K.
Abstract Objectives The effect of Aloe vera in epilepsy has not yet been explored. This study was done to explore the effect of aqueous extract of Aloe vera leaf powder on three acute and one chronic model of epilepsy. Methods In acute study, aqueous extract of Aloe vera leaf (extract) powder was administered in doses 100, 200 and 400 mg/kg p.o. Dose of 400 mg/kg of Aloe vera leaf extract was chosen for chronic administration. Oxidative stress parameters viz. malondialdehyde (MDA) and reduced glutathione (GSH) were also estimated in brain of kindled animals. Key findings In acute study, Aloe vera leaf (extract) powder in a dose‐dependent manner significantly decreased duration of tonic hind limb extension in maximal electroshock seizure model, increased seizure threshold current in increasing current electroshock seizure model, and increased latency to onset and decreased duration of clonic convulsion in pentylenetetrazole (PTZ) model as compared with control group. In chronic study, Aloe vera leaf (extract) powder prevented progression of kindling in PTZ‐kindled mice. Aloe vera leaf (extract) powder 400 mg/kg p.o. also reduced brain levels of MDA and increased GSH levels as compared to the PTZ‐kindled non‐treated group. Conclusions The results of study showed that Aloe vera leaf (extract) powder possessed significant anticonvulsant and anti‐oxidant activity.